2016
DOI: 10.3390/ijms17081291
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Methylation Approach Identifies a New Hypermethylated Gene Panel in Ulcerative Colitis

Abstract: The cause of inflammatory bowel disease (IBD) is still unknown, but there is growing evidence that environmental factors such as epigenetic changes can contribute to the disease etiology. The aim of this study was to identify newly hypermethylated genes in ulcerative colitis (UC) using a genome-wide DNA methylation approach. Using an Infinium HumanMethylation450 BeadChip array, we screened the DNA methylation changes in three normal colon controls and eight UC patients. Using these methylation profiles, 48 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 37 publications
(40 reference statements)
0
24
0
Order By: Relevance
“…To ensure consistency of data processing, we only compared our samples with publically accessible samples with raw idat files. GSE68060, GSE68838, GSE77954, GSE77965, GSE81211, GSE101764, GSE107352, and GSE75546 were collected from GEO while E-MTAB-6450 was collected from ArrayExpress [43][44][45][46][47][48] (Additional file 1: Table S6). Some cell line samples and metastatic cancer samples were removed upon further study.…”
Section: Public Datasets and Processingmentioning
confidence: 99%
“…To ensure consistency of data processing, we only compared our samples with publically accessible samples with raw idat files. GSE68060, GSE68838, GSE77954, GSE77965, GSE81211, GSE101764, GSE107352, and GSE75546 were collected from GEO while E-MTAB-6450 was collected from ArrayExpress [43][44][45][46][47][48] (Additional file 1: Table S6). Some cell line samples and metastatic cancer samples were removed upon further study.…”
Section: Public Datasets and Processingmentioning
confidence: 99%
“…18 Patients with IBD can be grouped as lifetime risk (2-to 3-fold greater) of developing CRC, and the most important risk factors for colitis-associated cancer are duration, severity and extent of the IBD. 13,14 There is a growing body of evidence suggesting that inflammation is the critical cause of many cancers, and colitis-associated cancer serves as a great model system to study the general principles understanding for the etiology of inflammation-associated cancer. 19 Prevalent evidence supports the theory that IBD is caused by a complex interplay between the predispositions of multiple genes and abnormal interactions with environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…The same investigators also identified 8 differentially methylated regions (DMRs) close to 8 different genes, and some of these genes were associated with immune-related pathways [71]. Regarding UC patients, Kang et al also found differentially methylated patterns in UC patients with 3 genes, FAM217B, KIAA1614 and RIBC2, being hypermethylated; thus, this might be a tool for distinguishing UC patients from healthy individuals [72]. In a recent study, mucosal biopsies taken from UC patients showed different methylation patterns from those of healthy individuals; UC patients showed hyper-methylation or hypo-methylation in genes involved in homeostasis and defense, or in immune response pathways, respectively [73].…”
Section: Epigenomics In Ibdmentioning
confidence: 99%